Comprehensive analysis of transcription factor binding sites and expression profiling of rice pathogenesis related genes (OsPR1) - Kumari, Diksha; Prasad, Bishun Deo; Dwivedi, Padmanabh; Sahni, Sangita; Kumar, Mankesh; Alamri, Saud; Adil, Muhammad Faheem; Alakeel, Khaled A. (Frontiers in Plant Science, 2024)
Pathogenesis-related (PR) proteins, found in plants, play a crucial role in responding to both biotic and abiotic stresses and are categorized into 17 distinct families based on their properties and functions. We have conducted a phylogenetic analysis of OsPR1 genes (rice PR1 genes) in conjunction with 58 putative PR1 genes identified in Brachypodium distachyon, Hordeum vulgare, Brassica rapa, and Zea mays through BLASTP predictions. We extensively investigated the responses of the remaining 11 rice PR1 genes, using OsPR1a as a reference, under various stress conditions, including phytohormone treatments (salicylic acid and brassinosteroid [BR]), wounding, and heat stress (HS). In rice, of the 32 predicted OsPR1 genes, 12 have been well-characterized for their roles in disease resistance, while the functions of the remaining genes have not been studied extensively. In our study, we selected an additional 11 OsPR1 genes for further analysis and constructed a phylogenetic tree based on the presence of a 10-amino-acid-long conserved motif within these proteins.The phylogenetic analysis revealed that both OsPR1a from earlier studies and OsPR1-74 from our current study belong to the same clade. These genes consistently exhibit upregulation in response to diverse stress treatments such as biotic stress and abiotic stresses such as heat, drought, and salinity, indicating their potential roles in enhancing stress tolerance in rice. Significantly, this study delves into the previously unexplored role of OsPR1 genes in responding to Brassinosteroid (BR) and heat stress (HS) treatments, confirming their involvement in stress responses through qRT-PCR analysis. We found that seven genes were upregulated by EBR treatment. During heat stress (HS), six and seven genes were upregulated at 1hand 4h HS, respectively. The remaining genes OsPR1-22 and OsPR1-75 were upregulated at 1h but downregulated at 4h HS and under EBR treatment. In contrast, OsPR1-76 was upregulated at both 1h and 4h HS, but downregulated under EBR treatment. Promoters of PR1 genes in rice and other crops are rich in transcription factor binding sites (TFBSs) and feature a conserved Cysteine-rich secretory protein (SCP or CAP) motif. This study advances our understanding of PR1 gene regulation and its potential to enhance stress tolerance in rice.